2015
DOI: 10.1007/s00066-015-0859-6
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric intensity-modulated arc therapy vs. 3-dimensional conformal radiotherapy for primary chemoradiotherapy of anal carcinoma

Abstract: VMAT was shown to be a feasible technique, achieving significantly lower rates of acute organ toxicity and promising results for LRC and DFS. Future investigations will aim at assessing the advantages of VMAT with respect to late toxicity and survival after a prolonged follow-up time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…On the other hand, in the exclusive setting of anal cancer, 4 chemoradiation studies (1 Phase I and 3 retrospective ones accounting for 103 patients) were analyzed. 78 81 One of them 80 investigated the irradiation of a single volume with either 2 full arcs or 4 half-arc VMAT technique and 6 MV photon energies. The delivered dose of 50.4 Gy at 1.8 per fraction caused mostly severe skin toxicity (29.4%), with low GI (11.8%) and GU (5.9%) severe toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the exclusive setting of anal cancer, 4 chemoradiation studies (1 Phase I and 3 retrospective ones accounting for 103 patients) were analyzed. 78 81 One of them 80 investigated the irradiation of a single volume with either 2 full arcs or 4 half-arc VMAT technique and 6 MV photon energies. The delivered dose of 50.4 Gy at 1.8 per fraction caused mostly severe skin toxicity (29.4%), with low GI (11.8%) and GU (5.9%) severe toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…In 3 studies, 78 80 elective lymph nodes received doses between 45 and 49.5 Gy (1.5 Gy/fraction); clinically detectable lymph nodes were treated with doses from 50.4 to 54 Gy (1.8–2 Gy/fraction), and macroscopic anal disease received doses from 50.4 to 59.4 Gy (1.8 Gy/fraction). Noteworthy, the SIB approach was able to shorten the overall treatment time with a consequent potential benefit on treatment outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…We included eight studies that compared chemoradiation with intensity-modulated radiotherapy (IMRT) to chemoradiation with 3D radiotherapy in stage I-III anal cancer patients. These included one single-centre RCT [58] (N = 20, risk of bias: 'some concerns'), three register-based cohort studies from the US [59][60][61] (moderate to serious risk of bias), and four single-centre retrospective cohort studies [62][63][64][65][66] (moderate to serious risk of bias). A significant advantage for IMRT was seen with respect to OS [HR 0.86 (0.76-0.98), GRADE: ⨁◯◯◯, 5,246 pts.…”
Section: Number Of Hits and Included Studiesmentioning
confidence: 99%
“…from 1 RCT [58]], DFS [HR 0.31 (0.09-1.05, GRADE: ⨁◯◯◯, 103 pts. from 1 observational study [64]], and CFS [HR 0.75 (0.07-8.18, GRADE: ⨁◯◯◯, 89 pts. from 1 observational study [62]].…”
Section: Number Of Hits and Included Studiesmentioning
confidence: 99%
“…Several studies have shown that VMAT performs equally in PTV coverage, with equal or possibly improved OAR sparing compared with that obtained using 3D CRT and IMRT 2 , 6 , 7 , 8 , 9 . In addition, VMAT delivers treatment with less beam‐on time and less monitor units (MUs) than IMRT.…”
Section: Introductionmentioning
confidence: 99%